2017
DOI: 10.1155/2017/9532381
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Sildenafil and Donepezil Improves Angiogenesis in Experimentally Induced Critical Limb Ischemia

Abstract: Objectives. In this study, we aimed to demonstrate the role of sildenafil (an antagonist of phosphodiesterase type 5 (PDE-5)) and donepezil (a specific and reversible inhibitor of acetylcholinesterase (Ach)) in increasing ischemia-induced angiogenesis. Method. Critical limb ischemia was induced by ligation of the common femoral artery followed by ligation of the common iliac artery. The operated animals were divided into 3 groups: receiving sildenafil, receiving donepezil, and surgery alone; the contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Accordingly, chronic administration of sildenafil improved ischemia-induced neovascularization in hypercholesterolemic apolipoprotein E-deficient mice, reduced TNF alpha staining in the femoral artery, and reduced inflammation and oxidative stress in skeletal muscle [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, chronic administration of sildenafil improved ischemia-induced neovascularization in hypercholesterolemic apolipoprotein E-deficient mice, reduced TNF alpha staining in the femoral artery, and reduced inflammation and oxidative stress in skeletal muscle [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be that chronic treatment might be mandatory. Indeed, beneficial effects of sildenafil were observed after daily, weekly, or even longer administration [31,32,33]. However, acute sildenafil administration also demonstrated some degrees of protection [44,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…no. LAT-18-5901; Lab Animal Technology Develop) ( 5 ). Finally, buprenorphine hydrochloride (0.1 mg/kg; cat.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical, although some therapeutic strategies exist, including surgical or interventional revascularization, substantial number of patients are not eligible for those treatments and amputation can be the only option ( 4 ). Previous studies have reported that therapeutic neovascularization is a promising option that could overcome ischemia by providing an improved vascular network ( 4 , 5 ). However, the process of neovascularization is complex and involves the induction of capillary sprouting (angiogenesis), the maturation of newly formed vessels and the growth of large-conductance vessels (arteriogenesis) to improve blood supply ( 6 - 8 ).…”
Section: Introductionmentioning
confidence: 99%